2018
DOI: 10.21037/tlcr.2018.03.23
|View full text |Cite
|
Sign up to set email alerts
|

The continued EGFR-TKI with cytotoxic chemotherapy at progression—poison or medicine?

Abstract: et al. Gefitinib plus chemotherapy versus chemotherapy in epidermal growth factor receptor mutationpositive non-small-cell lung cancer resistant to first-line gefitinib (IMPRESS): overall survival and biomarker analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Continuation of osimertinib plus chemotherapy regimen may rescue these patients who have received sequential EGFR-TKI therapy owing to poor response to chemotherapy. Although the phase 3 IMPRESS study demonstrated that continuation of gefitinib plus chemotherapy did not provide a better OS compared with chemotherapy alone (HR: 1.44, 95% CI: 1.07-1.94, P=0.016, median OS: 13.4 vs. 19.5 months), it cannot be determined whether the same results can be inferred using irreversible EGFR-TKIs in terms of improved central nervous system efficiency [18].…”
Section: Discussionmentioning
confidence: 98%
“…Continuation of osimertinib plus chemotherapy regimen may rescue these patients who have received sequential EGFR-TKI therapy owing to poor response to chemotherapy. Although the phase 3 IMPRESS study demonstrated that continuation of gefitinib plus chemotherapy did not provide a better OS compared with chemotherapy alone (HR: 1.44, 95% CI: 1.07-1.94, P=0.016, median OS: 13.4 vs. 19.5 months), it cannot be determined whether the same results can be inferred using irreversible EGFR-TKIs in terms of improved central nervous system efficiency [18].…”
Section: Discussionmentioning
confidence: 98%
“…AEs are shown in (31). A meta-analysis showed that, in advanced NSCLC, the median survival time was 13.26, 13.52, and 12.58 months for gefitinib, erlotinib and icotinib, respectively (25).…”
Section: Aesmentioning
confidence: 99%